Desain Penerapan Sistem Informasi Akuntansi Syariah di Rumah Sakit Islam Jawa Timur - Marina, Anna; Hiyatul Mubarokah, Fiky; Imam wahdjono, Sentot (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
Hospital is an organization or a non-profit oriented institution or commonly called a non-profit institution. The emergence of the need for hospital finansial reports that are in accordance with sharia principles has an important role in decision making, especially for hospital belonging to islamic organizations that are heading toward sharia are felt by several islamic hospital in East Java. The information system development methode use in this study is an iterative methode. In this study the research team made the application process using template Java, Admin Lite, Php 7x, CSS, dan juga MySql. Data collection through interviews with the team PLJSIAS and also through documentation by reading relate, journal and books. This study resulted in a sharia accounting information system that manages and reports hospital finances according to WEB-based sharia principles called SI AISYAH 2.0. In the implementation stage, an initial introduction to SI AISYAH application is needed to receive responses from hospital participant who take part in the training.